Natural variation of Alfin‐like family affects seed size and drought tolerance in rice. (28th October 2022) - Yang, Yunan; Ma, Xiaosong; Xia, Hui; Wang, Lei; Chen, Shoujun; Xu, Kai; Yang, Fangwen; Zou, Yuqiao; Wang, Yulan; Zhu, Jinmin; Li, Tianfei; Luo, Zhi; et al.
SUMMARY: The Alfin‐like (AL) family is a group of small plant‐specific transcriptional factors involved in abiotic stresses in dicotyledon. In an early study, we found an AL gene in rice that was associated with grain yield under drought stress. However, little information is known about the AL family in rice. In this study, AL genes in the rice genome were identified, and the OsAL proteins were found to locate in the nucleus and have no transcriptional self‐activation activity. The expression of the OsALs was regulated by different environmental stimulations and plant hormones. Association and domestication analysis revealed that natural variation of most OsALs was significantly associated with yield traits, drought resistance and divergence in grain size in indica and japonica rice varieties. Hap1 of OsAL7.1 and Hap7 of OsAL11 were favorable haplotypes of seed weight and germination under osmotic stress. Furthermore, osal7.1 and osal11 mutants have larger seeds and are more sensitive to abscisic acid and mannitol during germination stage. Overexpressing of OsAL7.1 and OsAL11 in rice weakened the tolerance to drought in the adult stage. Thus, our work provides informative knowledge for exploring and harnessing haplotype diversity of OsALs to improve yield stability under drought stress. Significance Statement: Adverse climatic environment is a significant threat to increased grain yield. We showed that a group of small plant‐specific transcriptional factors, the Alfin‐like (AL) family, is involved in regulating grain yield and drought resistance in rice. In this work, the Alfin‐like family was characterized, which OsAL proteins were found to locate in the nucleus and their expressions were regulated by different environmental stimulations and plant hormones. Moreover, natural variation of most OsALs was significantly associated with yield traits and drought resistance, and there were favorable haplotypes of OsAL genes to improve yield stability in rice variety resources.